2016
DOI: 10.4064/am2302-5-2016
|View full text |Cite
|
Sign up to set email alerts
|

A modified nonsymmetric rational block Lanczos method for model reduction in large scale LTI dynamical systems

Abstract: We propose an adaptive model reduction algorithm for computing a reduced-order model of dynamical multi-input and multi-output (MIMO) linear time independent (LTI) dynamical systems. The process is based on multipoint moment matching. Moreover, we develop new simple Lanczos-like equations for the rational block case, and we use them to derive simple residual error expressions. An adaptive method for choosing the interpolation points is also proposed. Finally, some numerical experiments are reported to show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For this reason, we modified the rational global Lanczos algorithm by allowing some interpolation points to be equal to infinity. Such a result is given in the study of Frangos and Jaimoukha for the standard form and extended to the block case in Barkouki et al The modified rational global Lanczos algorithm is summarized as follows.
…”
Section: The Modified Rational Global Lanczos Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, we modified the rational global Lanczos algorithm by allowing some interpolation points to be equal to infinity. Such a result is given in the study of Frangos and Jaimoukha for the standard form and extended to the block case in Barkouki et al The modified rational global Lanczos algorithm is summarized as follows.
…”
Section: The Modified Rational Global Lanczos Methodsmentioning
confidence: 99%
“…Recently, some rational Krylov methods were defined; see Grimme and Gallivan et al and the references therein, and it was shown that these rational‐based methods are more effective for model‐order reduction, and also for solving large Lyapunov and Riccati matrix equations . In the next section, we define the rational global Lanczos algorithm and we give some new algebraic properties.…”
Section: Moment Matching‐based Methodsmentioning
confidence: 99%
See 2 more Smart Citations